Exploring the Dynamics of Happiness Among People Living with HIV/AIDS (PLWHA): A Case Study of Residents at Kebaya Shelter House, Yogyakarta - Ikhlas Hariadi; Ayu Rezki Utari (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2026)
Previous studies have shown that happiness is closely related to health conditions, particularly among individuals with chronic illnesses who often experience psychological distress and unhappiness. HIV/AIDS is one of the chronic diseases, and previous research indicates that some people living with HIV/AIDS (PLWHA) fail to reconstruct their happiness. However, limited studies have explored the dynamics of happiness among PLWHA, especially within shelter-based settings. This study aims to understand the dynamics of happiness among PLWHA at Kebaya Shelter House, Yogyakarta. This research employs a qualitative method with a case study design. Data were collected through in-depth interviews, observations, and documentation based on Seligman’s (2011) theory of happiness. Data analysis was conducted through data reduction, data display, and conclusion drawing/verification. The results show that participants initially experienced negative psychological conditions such as shock, anxiety, stress, depression, and suicidal thoughts. Over time, through acceptance and adjustment processes, participants developed positive perspectives, rebuilt social relationships, engaged in meaningful activities, and regained happiness. This study emphasizes the importance of acceptance and social support in the process of achieving happiness among PLWHA. Future research is recommended to explore broader contexts and additional participants to strengthen findings.